2022
DOI: 10.3390/nu14081666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Enrichment with Flaxseed, Vitamin E and Selenium, and of Market Class on the Broiler Breast Meat—Part 1: Nutritional and Functional Traits

Abstract: The effect of dietary enrichment with flaxseed, selenium and vitamin E, and market class on the nutritional and functional value of breast meat was evaluated. A completely randomized block design was set up, where the experimental unit (n = 6000 birds) received conventional or enriched diet and was slaughtered at 37 (light class), 47 (medium class), or 57 (heavy class) days of life. Hence, functional and standard Pectoralis major muscles from every market class were analyzed for FA composition, inorganic eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
0
9
0
1
Order By: Relevance
“…Many studies have demonstrated the successful enrichment of meat with nutrients, such as polyunsaturated fatty acids, fat-soluble vitamins, minerals, etc. [ 6 , 7 ], when they added various plants/plant extracts or oils to the chickens’ feed. Dietary supplements from natural sources are appreciated by consumers who consider them safe and nutritious.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the successful enrichment of meat with nutrients, such as polyunsaturated fatty acids, fat-soluble vitamins, minerals, etc. [ 6 , 7 ], when they added various plants/plant extracts or oils to the chickens’ feed. Dietary supplements from natural sources are appreciated by consumers who consider them safe and nutritious.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental design of the study was already described in our previous study [ 7 ]. Briefly, a total of 36,000 of 1-day old and mixed sex broiler chicks (breed: Ross 308) were farmed and slaughtered in dedicated plants of the company “Avimecc S.p.A.” (Ragusa, Italy) during June–July 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, a Shapiro–Wilk test was run to verify the initial assumptions of experimental data. Then, the GLM procedure of the SAS statistical package (SAS Institute Inc., Cary, NC, USA) was employed to analyze data according to a multiple linear regression as already described by Albergamo and colleagues [ 7 ]. The model included data from breast muscles as dependent variables, and the diet program, the market size, the storage, and their mutual interaction as fixed factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing consumer awareness of food quality, production trends, the relationship between diet and health, and lack of time are the most common reasons for introducing new, more nutritional products to the market, as well as easy-to-prepare meat products [ 1 , 2 , 3 ]. The addition of natural bioactive compounds to meat products is nowadays a popular trend in meat processing [ 4 , 5 , 6 ]. Currently, enriched meat products are obtained thanks to modification at the raw material production stage (appropriate selection of animal breed, in terms of the animal raw materials obtained) and selection and supplementation of feed [ 6 , 7 ], and enrichment of meat products at the processing stage.…”
Section: Introductionmentioning
confidence: 99%